Air Humidity Measurement Through Solar Panel - Panjaitan, Christin Erniati; Saputra, Daniel Jaya; Hasudungan, Bangun D; Tarigan, Sri Wahyuni; Napitupulu, Janter (SHM Publisher, 2024)
In this work, we will examine the placement of solar panels at certain heights to obtain optimal efficiency. To prove the effect of altitude and humidity, the authors conducted tests in areas with different altitudes and different temperatures, namely in the areas of Medan and Berastagi cities, where the city of Medan is located at an altitude of 2.5-7.5 meters above sea level, and the city area of Berastagi is higher, namely at an altitude of 1220 meters above sea level. The distance between the two areas is around 70 km and can be reached in approximately 2 hours of travel. With different altitudes and different climates, the authors are very interested in studying and researching how the effectiveness of solar panels is at different altitudes and humidity level and how it affects the Medan area, which has a tropical climate, and Berastagi, which has a cold climate.